ANALISIS PENERAPAN SAK ETAP PADA KSU DHARMA WANITA PERSATUAN KABUPATEN SOLOK SELATAN - Tama, Asmy Febry (Jurnal Manajemen Perbankan Keuangan Nitro, 2025)
In this study, the researcher focuses on the analysis of the application of Indonesian Accounting Standard for Non-Publicly-Accountable Entities (SAK ETAP) at KSU Dharma Wanita Persatuan, South Solok Regency. Data was obtained through the Accountability Report of the Management of KSU Dharma Wanita Persatuan, South Solok Regency for the 2021, 2022 and 2023 Financial Years, as well as interviews with its financial management. The analysis method used here is descriptive comparative. The results of the study indicate that KSU Dharma Wanita Persatuan, South Solok Regency has not made a financial report because the Accountability Report made by the Management of KSU Dharma Wanita Persatuan, South Solok Regency cannot be said to be a Cooperative Financial Statement, this is because the report does not meet the reporting standards described in SAK ETAP. The report made is not yet standard due to the lack of skilled and expert workers in accounting, the absence of education and socialization from the government and related parties regarding the implementation of SAK ETAP, and the lack of knowledge of management in financial reports included in SAK ETAP, so that the report made is only based on reports from previous years and it is understood as a financial report